Factors influencing companies to be public listed companies - Syazrul Afif Ismail @ Abdul Raof, 1994-, author 612057; Mohd. Effandi Yusoff supervisor 636512; Fakulti Pengurusan 538641 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2018